Visualising the invisible - Kandzha, Iliana (Ikon;Rijeka, 2021;Band 14 (2021), Seite 189-200, 2021)
The concept of virginity is crucial for understanding medieval societies, as it constituted an important social commodity, a laudable Christian virtue, and a signature quality of many saints. While multiple connotations of virginitas coexisted throughout the medieval period, the strategies employed to visually communicate this physical and moral quality were equally diverse. This paper investigates various representational strategies that were chosen to depict one female saint - St Cunigunde (c. 980-1033, canonised 1200) - in the late medieval German-speaking lands. This paper argues that St Cunigunde’s multifaceted profile allowed for several interpretations of her virginity: embodying bodily purity, spiritual excellence, honorary virginity, and marital fidelity. Each of these interpretations was communicated through distinct representational strategies, depending on devotional and iconographic contexts. By the end of the medieval period, an image portraying Cunigunde undergoing an ordeal of burning ploughshares to prove her virginity proliferated. This iconographic type became popular because, on the one hand, it made Cunigunde easily recognisable, and, on the other, it associated her with a well-known type of virgin martyr, since the sexual abstinence of St Cunigunde and the ordeal she went through were understood as being comparable to the act of martyrdom. Unique artistic commissions devoted to St Cunigunde allowed for more interpretations of her virginity, relying on the audience’s knowledge of the legends and the commissioner’s own intentions, experiences, and ideals.
Keywords: Kunigunde; Heiligenbild; Jungfräulichkeit; Heiligenvita